2017
DOI: 10.1021/acs.langmuir.7b03014
|View full text |Cite
|
Sign up to set email alerts
|

Salvinia-Effect-Inspired “Sticky” Superhydrophobic Surfaces by Meniscus-Confined Electrodeposition

Abstract: Inspired by the Salvinia effect, we report the fabrication and characterization of a novel "sticky" superhydrophobic surface sustaining a Cassie-Baxter wetting state for water droplets with high contact angles but strong solid-liquid retention. Unlike superhydrophobic surfaces mimicking the lotus or petal effect, whose hydrophobicity and droplet retention are typically regulated by hierarchical micro- and nanostructures made of a homogeneous material with the same surface energy, our superhydrophobic surface m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…[21][22][23] These strategies may also increase the hydrophobicity of an electrode, however this is rarely discussed as a determinant on selectivity. Submerged hydrophobic surfaces trap appreciable amounts of gas at the nanoscale, 24,25 and even at the microscale if the Cassie-Baxter regime is reached, 26 allowing trapped CO 2 to accumulate at the Cu|solution interface. Recent reports have exploited gas|electrode|solution triple-phase boundaries to increase the CO 2 reduction activity of Cu on gas diffusion electrodes with hydrophobic polytetrafluoroethylene layers, 19,20 however it is difficult to assign this enhancement solely to hydrophobicity over other factors, such as their porosity and increased mass transport.…”
Section: Figure | Co 2 Reduction As a Source Of Sustainable Fuel And mentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] These strategies may also increase the hydrophobicity of an electrode, however this is rarely discussed as a determinant on selectivity. Submerged hydrophobic surfaces trap appreciable amounts of gas at the nanoscale, 24,25 and even at the microscale if the Cassie-Baxter regime is reached, 26 allowing trapped CO 2 to accumulate at the Cu|solution interface. Recent reports have exploited gas|electrode|solution triple-phase boundaries to increase the CO 2 reduction activity of Cu on gas diffusion electrodes with hydrophobic polytetrafluoroethylene layers, 19,20 however it is difficult to assign this enhancement solely to hydrophobicity over other factors, such as their porosity and increased mass transport.…”
Section: Figure | Co 2 Reduction As a Source Of Sustainable Fuel And mentioning
confidence: 99%
“…Similar activation has been documented on other hydrophobic electrodes. 26 The hydrophobic dendrite therefore requires an initial application of potential to generate a stable liquid|electrode|gas triple-phase boundary at the top of the dendrite where electrochemical reactions take place, as illustrated in Figure 2j. This activation was monitored through one day of repeated LSV scans, wherein the current at -1.4 V vs. RHE stabilised 3-5 times lower than that of the wettable equivalent (Supplementary Figure 10).…”
Section: Preparation and Characterization Of The Hydrophobic Cu Dendritementioning
confidence: 99%
“…The multiscale hierarchy also helps the FDTS-coated surface to have the slippery superhydrophobicity with modulated CA and droplet mobility (CAH/SA), mimicking the lotus effect. The efficient controllability of the superhydrophobicity and droplet mobility on polymer surfaces, enabled by the maskless plasma-based etching process assisted by the combination with conventional lithography and the modulation of hydrophobic coating process, will be of great significance in many applications, such as slippery superhydrophobicity for anti-icing surfaces [ 56 ], enhanced condensation [ 57 ], droplet manipulation [ 58 ], and fog harvesting [ 59 ], and sticky superhydrophobicity for no-lost transportation of droplets [ 49 ], preparation of protein micro-array [ 50 ], in-situ detection [ 51 ], and localized reactions [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salvinia leaves) has directly influenced the choice of selected materials/chemicals and fabrication methods, which helped to improve the air retention ability. [142][143][144][145] (2) Controlling plastrons' environment: other methods attempt to work on the environmental conditions around the plastrons and how to make them less detrimental for plastrons' lifetime. In this case, the target is to record higher failure/ breakdown pressures than what would be achieved solely by optimising design/fabrication conditions.…”
Section: Approaches For Underwater Stability In Manufactured Surfacesmentioning
confidence: 99%
“…Among these examples, many reports expressed a great interest in the intricate structure of Salvinia leaf and its resultant underwater stability. [142][143][144] The ''Salvinia effect'' has received particular attention as it has excellent air layer stability but does not display extreme waterrepelling properties, with reported WCAs of r1401. 76,149 From investigations of the leaf properties and structure, it was concluded that five factors are essential for any surface to show the Salvinia effect: (i) choosing an inherently hydrophobic material, (ii) inducing a high aspect-ratio feature (hair, filament, etc.…”
Section: Systems Inspired By Naturementioning
confidence: 99%